Electrophoretic protein pattern and acid phosphatase activity in the midgut extracts of Apis mellifera L. (Hymenoptera : Apidae) during metamorphosis - Cavalcante, V. M.; Da Cruz-Landim, C. (Entomological Soc Brasil, 2004)
The electrophoretic pattern of proteins and the activity of acid phosphatase were described in the midgut extracts during the post-embryonic stages of Apis mellifera L. in order to stablish a correlation with the metamorphosis events. The results show the greatest variation in proteic electrophoretical bands during prepupal stage and the smallest variation during the brown eyed pupae stage. The acid phosphatase activity was higher during the larval last instar and lower in white eyed pupae. The greatest variety of bands during the prepupal stage coincides with the histolysis of the larval midgut epithelium and the lowest variability in the brown eyed pupa coincides with the end of the midgut differentiation. In another hand, the greatest phosphatase activity in the last larval stage must reflect this enzyme actuation in the histolysis of the larval epithelium.
Keywords: differentiation; enzymes; histolysis; larva; prepupa; post-embryonic development; pupa